Poverty Reduction, Shared Prosperity and Inequality in FYR Macedonia in the Post Financial Crisis Period (2009-2013) - World Bank (World Bank, Washington, DC, 2017)
FYR Macedonia has experienced a decline in poverty in the post global financial crisis period (2009-2013) in spite of a weak macroeconomic performance. In contrast to the pre-crisis period when growth was robust but poverty stagnant, poverty indicators indicate an improvement on the living conditions of the bottom of the distribution. Employment gains were the main reason for the increase in welfare among the less well-off, while other income sources like pensions, social assistance or remittances have played a limited role. Labor income at the bottom of the distribution continues to be very low, however, and the sustainability of the employment gains is uncertain as the public sector played an important role for employment expansion in the period. Still, FYR Macedonia faces many challenges looking forward. Despite the recent improvements, poverty and inequality is still high when compared with other countries with similar levels of GDP per capita in the region. Income-generation opportunities for the poor are limited as the poor have very weak labor market attachment, their employment quality is lower than for the rest and are more likely to be employed in low productivity sectors. Inclusive growth seem also to be challenged by the differences in access to high wage jobs for women and the youth. Demographics seem important looking forward, since they will shape future labor markets performance.